Advanced maternal age: copy number variations and pregnancy outcomes - Cao, Luoyuan; Dong, Wenxu; Wu, Qinjuan; Huang, Xiaomin; Zeng, Xiaomei; Yang, Jing; Lu, Jiaojiao; Chen, Xunyan; Zheng, Xian; Fu, Xianguo (Frontiers in Genetics, 2023)
Objective: Adverse pregnancy outcomes are closely associated with advanced maternal age (AMA; age at pregnancy ≥35 years). This study aimed to evaluate copy number variations (CNVs) associated with AMA in prenatal diagnosis to determine the characteristics of pathogenic CNVs and assist with genetic counseling of women with AMA. Methods: Among 277 fetuses of women with AMA, 218 (78.7%) were isolated AMA fetuses and 59 (21.3%) were non-isolated AMA fetuses and showed ultrasound anomalies from January 2021 to October 2022. All fetuses underwent conventional karyotyping followed by single-nucleotide polymorphism array (SNP-array) analysis. Results: Of the 277 AMA cases, karyotype analysis identified 20 chromosomal abnormalities. In addition to 13 cases of chromosomal abnormalities consistent with karyotype analysis, the SNP array identified an additional 14 cases of CNVs with normal karyotyping results, of which 5 were pathogenetic CNVs, 7 were variations of uncertain clinical significance (VOUS), and 2 were benign CNVs. The detection rate of abnormal CNVs in non-isolated AMA cases was higher (14/59; 23.7%) than in isolated AMA cases (13/218; 5.96%) (P = 0.000). We also determined that pathogenic CNVs affected the rate of pregnancy termination in women with AMA. Conclusion: Aneuploid abnormalities and pathogenic CNVs affect pregnancy outcomes in women with AMA. SNP array is necessary and effective for identifying pathogenic CNVs in fetuses with AMA and enables more informed clinical counseling and decision-making.